Blood cortisol concentration in response to recurrent manipulation in crossbred Holstein embryo donors - Garay–Peña, Gabriela Sofía; Jácome–Aucay, Andrés Santiago; Dután–Sanango, Jorge Bolívar; Rodas–Carpio, Ermes Ramiro; Ayala–Guanga, Luis Eduardo (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
The neuroendocrine response of the donor was determined by reducing the number of applications of follicle–stimulating hormone (FSH) as a superovulation factor. 8 crossbred Holstein cows were randomly distributed in two treatments (T): T1 (n=4) received a dose of 200 mg of FSH via epidural (EP) on day 4 of the superovulation protocol (SOV), in T2: 300 mg of FSH were administered divided into 8 decreasing doses intramuscularly (IM), on days 4; 5; 6 and 7 of the protocol in the morning and afternoon. The Cortisol concentration was determined at 0, 2, 4, 6.24, 26, 28, 30, 48, 50, 52, 64, 72, 74, 76 and 78 hours (h) of day 4. Heart rate (HR), respiratory rate (RR) and glucose levels were evaluated on day 4 at 05:45; 06:05; 08:00; 10:00 a.m.; 12:00; 5:45 p.m. and 6:05 p.m. Cortisol at 0h was similar in both T: T1 (10.9 ± 0.24 µg·dL-1) and T2 (10.8 ± 0.33 µg·dL-1) and reached its highest level at 4h in T1 (15.8 ± 1.39 µg·dL-1) and at T2 (16.4 ± 0.28 µg·dL-1) with no difference between T (P>0.05). In the following evaluations, Cortisol decreased to basal levels in the two T. HR at 05:45h showed similar values in T1 (65.3 ± 1.65 pul·min-1) and in T2 (66.3 ± 1.43 pul·min-1); however, at 06:05 HR increased in T1 (74.3 ± 1.54 pul·min-1) and in T2 (84.2 ± 1.73 pul·min-1) and decreased from 08:00. The same behavior was observed with RF and Glucose. It is concluded that taking the donor to the support sleeve to administer FSH is a stressful factor that increases HR, RF, Cortisol and Glucose, factors that influence the percentage of ovulations in the two T.